Glucocorticoid-Induced Osteoporosis – A Disorder of Mesenchymal Stromal Cells? - Cooper, Mark S.; Hardy, Rowan (Frontiers in Endocrinology, 2011)
Glucocorticoids are a class of steroid hormones that are essential to life but cause serious harm in excess. The main clinical features of glucocorticoid excess are due to adverse effects on cells and tissues that arise from a common developmental precursor – the mesenchymal stromal cell (MSC; sometimes referred to as the mesenchymal stem cell). Interestingly glucocorticoids appear essential for the differentiation of cells and tissues that arise from MSCs. High levels of glucocorticoids are used in tissue engineering strategies to enhance the formation of tissues such as bone, cartilage and muscle. This article discusses the paradox that glucocorticoids both enhance and impair MSC development and function. It will describe how endogenous glucocorticoids are likely to be important in these processes in vivo and will discuss the implications for therapies aimed at reducing the damage associated with the use of therapeutic glucocorticoids.